2017
DOI: 10.1038/s41598-017-05606-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimized analysis of blood flow and wall shear stress in the common carotid artery of rat model by phase-contrast MRI

Abstract: The present study systemically investigated the influence of gated/non-gated sequences, velocity encoding (VENC), and spatial resolution on blood flow, wall shear stress (WSS), and artery area evaluations when scanning the common carotid artery (CCA) in rats using phase-contrast magnetic resonance imaging (PC-MRI). We first tested whether or not non-gated PC-MRI was appropriate for evaluating blood flow and WSS in rats. For both gated and non-gated techniques, VENC values in the range of 60-120 cm/s with an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
13
0
1
Order By: Relevance
“…Therefore, in this study we performed four separate PC‐MRI scans in which each targeted one artery only, which guaranteed that the image slice would be perpendicular to the vessel orientation. Most notably, both lower and higher spatial resolutions have significant effects on flow measurement reliability . In this study we used an optimized spatial resolution of 0.5 mm, which is a compromise between accuracy, repeatability, and time consumption .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study we performed four separate PC‐MRI scans in which each targeted one artery only, which guaranteed that the image slice would be perpendicular to the vessel orientation. Most notably, both lower and higher spatial resolutions have significant effects on flow measurement reliability . In this study we used an optimized spatial resolution of 0.5 mm, which is a compromise between accuracy, repeatability, and time consumption .…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, both lower and higher spatial resolutions have significant effects on flow measurement reliability. 36 In this study we used an optimized spatial resolution of 0.5 mm, which is a compromise between accuracy, repeatability, and time consumption. 15 Consequently, all of these improved technological considerations enabled better reproducibility in the examinations conducted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Oshinski et al reported a spatial-average-time-average WSS of 8.0 ± 4.1 dynes/cm² in the CCA of healthy volunteers measured using MRA imaging [24]. Here, we decided to compute the WSS from Doppler ultrasound data and not from MRA data [25][26][27][28]. Our purpose was to establish a reliable method of WSS calculation based on a noninvasive, low-cost, easily accessible examination with little or no post-processing tasks.…”
Section: Limitations and Strength Of The Present Studymentioning
confidence: 99%
“…First, 2D techniques using triggered radial PC MRI [ 68 ] or Cartesian flow cine MRI [ 71 ] were developed to study WSS in the abdominal aorta of wild-type, ApoE −/− - and Low-density lipoprotein receptor-deficient (Ldlr −/− ) mice. WSS was also assessed in the carotids of mice with unstable plaques using Gd-enhanced 2D flow MRI [ 72 ] and in the carotids of rats [ 73 ]. Furthermore, 2D flow MRI was used to determine WSS at different locations along the vascular tree in arteries and veins in wild-type mice, revealing significant sex- and age-related differences of the WSS and flow values [ 74 ].…”
Section: The Role Of Shear Stress In the Development And Progressimentioning
confidence: 99%